Assessment of antimicrobial use and stewardship practices among animal health practitioners, veterinary drug retailers and cattle keepers in Mvomero, Tanzania - Mugyabuso, Asimwe M.; Makundi, Isaac; Hoza, Abubakar S. (Frontiers in Antibiotics, 2026)
BackgroundAntimicrobial misuse in livestock is a key driver of antimicrobial residues and resistance (AMR), yet knowledge, attitudes, and practices (KAP) among cattle keepers and stewardship awareness among animal health practitioners (AHPs) and veterinary drug retailers ((VDR) remain poorly characterized in many low-resource settings.MethodsA total of 322 participants were interviewed in a cross-sectional study using semi-structured questionnaires and open-ended interviews. They included, 299 cattle keepers, 10 AHPs and 13 VDR. Descriptive statistics were done to compute frequencies of responses, chi square tests and linear regression analysis to assess association between dependent and independent variables while thematic analysis to analyze key informants’ interviews.ResultsAwareness of antimicrobial use (AMU), residues, and AMR was generally low, with a mean score of 94 (31.4%, 95%CI: 26.2-36.6). The Mean awareness score from Linear regression showed that higher education (secondary: β = 0.878, p = 0.002; tertiary: β = 1.469, p < 0.001) and longer livestock experience (>4 years: β = 1.35, p < 0.001) were positively associated with awareness, whereas younger age groups had lower scores. Awareness significantly predicted attitudes toward responsible AMU, particularly regarding residues (β = 6.427, p < 0.001) and AMR (β = 2.473, p < 0.001). Attitudes were generally low, with an overall mean score of 2.06 (41.2%). Male sex, older age, higher education, and longer livestock experience were positively associated with more favorable attitudes. Practices were suboptimal: 99.7% (95%CI: 99.1-100) reported AMU, but only 21.1% (95%CI: 16.4-25.8) kept treatment records, hygiene was limited, and manure was frequently applied to fields (77.6%, 95%CI: 72.8-82.3). Key informants highlighted frequent non-prescription sales (AHPs: 9/10; VDR: 13/13), reliance on empirical diagnosis (AHPs: 10/10; VDR: 3/10), weak regulatory enforcement (AHPs: 8/10; VDR: 11/13), and limited knowledge of AMR (AHPs: 6/10; VDR: 3/13) as major drivers of inappropriate AMU.ConclusionAwareness, age, education, and livestock experience significantly influenced attitudes toward responsible AMU. Systemic gaps in veterinary services emphasize the need for integrated educational and regulatory interventions to improve antimicrobial stewardship and mitigate AMR risks.